Comparisons of lysine bioavailability in spray-dried blood meal, blood cells, and crystalline lysine in nursery pigs - Woodworth, J.C.; James, B.W.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred thirty-three nursery pigs (initially 23.7 lb) were used in a 21-d growth assay to determine the lysine bioavailability of spray-dried blood meal, blood cells, and crystalline lysine on growth performance. Regardless of lysine source, ADG improved linearly as dietary lysine increased. However, pigs fed diets containing blood cells gained faster then those fed diets with spraydried blood meal. Pigs fed diets containing crystalline lysine and blood cells had greater ADFI then pigs fed spray-dried blood meal. Feed efficiency improved by 11.6, 13.6, and 12.7% with increasing amounts of L-lysine HCl, spray-dried blood meal, and blood cells, respectively. If L-lysine has a lysine bioavailability of 100%, the lysine bioavailabilities of spray-dried blood meal and blood cells, as determined by a sloperatio, were 103 and 102%, respectively.
Keywords: Swine; Nursery pigs; Lysine; Spray-dried blood meal; Blood cells